Involving Parents in a Summer Book Reading Program To Promote Reading Comprehension, Fluency, and Vocabulary in Grade 3 and Grade 5 Children - Pagan, Stephanie; Sénéchal, Monique (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
In this research, parents and children participated in a comprehensive book reading intervention designed to improve children’s literacy. Over eight weeks during the summer, children in the intervention condition were encouraged to read one book weekly and parents were trained to foster reading comprehension. Forty-eight Grades 3 and 5 children were selected for their lower performance on expressive vocabulary and reading comprehension. Participating children were randomly assigned to the intervention or control condition. As predicted, children in the intervention condition made significantly greater gains than children in the control condition in reading comprehension, reading fluency, and receptive vocabulary.